Video-based feedback combined with reflective enquiry - An interactive model for movement awareness among nursing students - Sofia Backåberg; Mikael Rask; Christina Gummesson; David Brunt (Universitetsforlaget, 2015)
The aim of this study is to describe an interactive model developed for movement awareness in a practical learning situation and to explore the use of video-based digital feedback and reflective enquiry in this model among nursing students. Sixteen students participated in individual interactive video sessions with a facilitator, who encouraged the students to reflect upon their own movements. Qualitative analysis showed that movement patterns were visualized, and that movement awareness and self-analysis were gradually developed. Encountering one's own movement and reflecting on one's own experiences appear to support motivation for movement changes.